Study of Brain Radio Signals Using Bispectral Analysis - Hovhannisyan, B. A.
Using a special sensor (probe antenna-applicator), radio signals emitted by the human brain are recorded. The changes of different parameters are investigated while studying different physical and emotional states of people. The studies are carried out using spectral and bispectral analysis in the LabVIEW environment. It is shown that in a stressful state the bispectrum of the brain’s radio signal is significantly enriched, and many phase coupled spectral components appear. They undergo changes in their amplitude and frequency. The results of these studies may be useful for understanding the nature and identification of fast processes in the human brain.
Keywords: Physics